The urban weave: Interlacing intangible threads to form a cohesive hybridized urban fabric - Ndawonde, Nosipho (School of Architecture, Planning and Geomatics, 2024)
The objective is to find tangible ways of seamlessly tying informal systems within formal systems in an urban space that will result in a paradigm shift of the way informality is viewed by the public. The intervention seeks to find a balance between the creativity of emergence and the stability of design. Where architecture does not control how the user operates in the spaces but rather becomes a guiding tool and give people ownership of their spaces. The goal is to work towards preserving and creating a strong African identity even with the influences of modern technology and influences.